2012
DOI: 10.1111/j.1470-6431.2011.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of traceability for sustainable production: a cross‐country comparison

Abstract: Traceability systems are becoming an important tool for tracking, monitoring and managing product flows through food supply chains. Traceability can be used as a method of certifying production, processing and nutritional credence attributes of food products. Environmentally sustainable production is a credence attribute that is gaining in importance in the eyes of consumers. In this research, the importance of traceability in verifying environmentally sustainable production practices is examined. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Farmers must provide customers benefits in return for loyal support, which is consistent with SET (Cropanzano & Mitchell, ; Emerson, ; Roloff, ). Farmers provide access to a food supply that consumers perceive as high quality (Brown, ; Feagan & Morris, ), environmentally friendly (Alkon, ; Garner, ), and healthy (Alonso & O'Neill, ; Brown, ; Myae & Goddard, ). Farmers also provide customized service to loyal customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers must provide customers benefits in return for loyal support, which is consistent with SET (Cropanzano & Mitchell, ; Emerson, ; Roloff, ). Farmers provide access to a food supply that consumers perceive as high quality (Brown, ; Feagan & Morris, ), environmentally friendly (Alkon, ; Garner, ), and healthy (Alonso & O'Neill, ; Brown, ; Myae & Goddard, ). Farmers also provide customized service to loyal customers.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers’ markets are growing rapidly in the United States (USDA, ), as well as in Canada, the U.K., and New Zealand (Feagan & Morris, ; Guthrie, Guthrie, & Lawson, ). The local food movement and farmers’ markets are a growing niche market in which scholars can and have examined consumer values such as: community and embeddedness (Feagan & Morris, ; Lyson, Gillespie, & Hilchey, ; Robinson & Hartenfeld, ), sustainability and environmentalism (Alkon, ; Garner, ), localism (Hinrichs, ; McEachern, Warnaby, Carrigan, & Szmigin, ), health and product quality (Brown, ; Myae & Goddard, ; Weber, Heinze, & DeSoucey, ), politics (Brenton, ; Pezzullo, ; Pezzullo, ) and especially increased social interaction and interdependence with vendors (Garner, ; Hunt, ; Sommer, Herrick, & Sommer, ; Trobe, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that when a fast food store adopts FTS, consumers' perceived uncertainty can be reduced because both their perceived information asymmetry and fear of seller opportunism also fall, which in turn strengthens their purchase intentions regarding fast foods. In regards to environmental issues, Myae and Goddard [7] discovered which factors influence the degree of importance consumers place on traceability in guaranteeing environmentally sustainable production methods. In a country comparison (Canada, US and Japan), there are significant differences in countries' interests in traceability when verifying environmentally sustainable production practices and in the determinants for level of importance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As one to the tools adopted by the food industry to improve food safety, traceability plays an important role because it complies with legislation and it enhances the transparency and safety of the food system through the provisions of transparent trace back and track forward information as well as to boosting consumer confidence [1][3] [7]. In many countries, traceability systems have been introduced as a legal requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain transparency and security have emerged as key concerns for various industries. With growing number of ethical issues and increasing counterfeits, it has become a necessity to make the supply chains more secure and transparent [1][2][3]. Textile and clothing (T&C) supply chain is one such example.…”
Section: Introductionmentioning
confidence: 99%